2020
DOI: 10.1007/s10653-020-00692-2
|View full text |Cite
|
Sign up to set email alerts
|

Pollution status and human health risk assessment of potentially toxic elements and polycyclic aromatic hydrocarbons in urban street dust of Tyumen city, Russia

Abstract: This study investigated levels and sources of pollution and potential health risks associated with potentially toxic elements (PTEs) and polycyclic aromatic hydrocarbons (PAHs) in urban street dust collected from Tyumen city, a large transport centre with one of the highest motorization rates in Russia. Twenty street dust samples were collected from four grades of roads in five different land use areas.Research methods included measurements of physical and chemical properties of street dust, concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…The objectives of the presented work are to identify the features of HMM accumulation in road dust, depending on the tra c intensity and the location of other polluting objects, to assess the ratio of natural and anthropogenic sources, to evaluate the level of pollution. The present study complements and expands the work of Konstantinova et al (2020) by: (a) collecting a large number of samples from a wider area around the city of Tyumen (50 sampling sites); (b) measuring the concentrations of other major and trace elements (Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Sc, Sr, Ti, U, V and Zn) in the road dust; (c) estimates of the ratio of natural and anthropogenic sources of HMMs in road dust.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The objectives of the presented work are to identify the features of HMM accumulation in road dust, depending on the tra c intensity and the location of other polluting objects, to assess the ratio of natural and anthropogenic sources, to evaluate the level of pollution. The present study complements and expands the work of Konstantinova et al (2020) by: (a) collecting a large number of samples from a wider area around the city of Tyumen (50 sampling sites); (b) measuring the concentrations of other major and trace elements (Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Sc, Sr, Ti, U, V and Zn) in the road dust; (c) estimates of the ratio of natural and anthropogenic sources of HMMs in road dust.…”
Section: Introductionsupporting
confidence: 78%
“…According to the classi cation of Hakanson (1980), in terms of Cf, the content of Co, Cu, Zn, As, Mo, Ag, Cd, Sn, W, Pb Bi corresponds to the level of "moderate contamination", Cr -"signi cant contamination" and Ni, Sb -"very high contamination". The pollution of road dust in Tyumen with chromium and nickel was previously noted by Konstantinova et al (2020), who revealed that the concentration of these elements is 4 and 7 times higher, respectively, compared to urban soils. An increased content of Cr, Ni, Pb, V was also noted in the snow cover (Guseinov et al 1997), which con rms the atmospheric input of these metals.…”
Section: Trace Elements Content In Road Dustmentioning
confidence: 61%
See 1 more Smart Citation
“…This indicates the significant role of wet deposition processes for the PTEs input into terrestrial landscapes. The main sources of most of these PTEs are vehicle emissions, fuel combustion, tires and brake pads wear, road surface abrasion, roadside soil particles blowing, industrial enterprises emissions, as well as macroregional long-distance transport of pollutants (Demetriades and Birke 2015;Grigoratos and Martini 2015;Grivas et al 2018;Konstantinova et al 2020;Liyandeniya et al 2020;Logiewa et al 2020;Orlović-Leko et al 2020;Ramírez et al 2020;Seleznev et al 2020;Tian et al 2020), which is confirmed by the previously identified sources of snow cover pollution in the western part of Moscow (Vlasov et al 2020). The remaining PTEs on the territory of the MO MSU were apparently of mixed anthropogenic-terrigenous sources (P 38 , Ba 31 , As 30 , W 22 , Mn 20 , Sn 19 , Na 16 , Co 14 , Ni 12 , Be 11 , K 11 ) and terrigenous origin (Rb 6 , Cr 4 , Fe 3 ), which indicates the influence of solid particles blown out from the Earth's surface and included in the atmospheric precipitation.…”
Section: Sources Of Ptes In Rainwatersupporting
confidence: 56%
“…Input of a large group of MMs as a result of blowing and splashing mud material from the surface of roads is indicated by the formation of associations of suspended Ni-Al-Mg-Ti-Ca-Sr-Mn-Co-W-K-Rb-Ba-Ni-Fe-V and dissolved Ti-Fe-Pb-Al-Sn-Bi-W. Thus, Al, Ti, Fe, Mn, Rb, and K come predominantly with soil particles upon blowing [118][119][120]; Na, Ca, Mg, and Sr-with construction dust and large DISs particles; W, Sn, Bi, Co, Ni, Ba, Pb, and Ti-with various size fractions of road dust [67,95,119,[121][122][123][124][125].…”
Section: Indication Of Sources (Cluster Analysis)mentioning
confidence: 99%